1995
DOI: 10.1128/jb.177.18.5322-5326.1995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an ntrBC mutation on the posttranslational regulation of nitrogenase activity in Rhodospirillum rubrum

Abstract: Homologs of ntrB and ntrC genes from Rhodospirillum rubrum were cloned and sequenced. A mutant lacking ntrBC was constructed, and this mutant has normal nitrogenase activity under nif-derepressing conditions, indicating that ntrBC are not necessary for the expression of the nif genes in R. rubrum. However, the posttranslational regulation of nitrogenase activity by ADP-ribosylation in response to NH 4 ؉ was partially abolished in this mutant. More surprisingly, the regulation of nitrogenase activity in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 39 publications
0
34
1
Order By: Relevance
“…Previous studies showed that NtrBC are not essential for nif expression in R. rubrum, indicating that R. rubrum has a different regulatory mechanism for nif expression from that seen in K. pneumoniae (59). In R. rubrum, transcription of nifA is not regulated but NifA activity is tightly controlled in response to NH 4 ϩ (62).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies showed that NtrBC are not essential for nif expression in R. rubrum, indicating that R. rubrum has a different regulatory mechanism for nif expression from that seen in K. pneumoniae (59). In R. rubrum, transcription of nifA is not regulated but NifA activity is tightly controlled in response to NH 4 ϩ (62).…”
mentioning
confidence: 97%
“…The NtrB-NtrC regulatory system is tightly controlled by the status of P II modification in E. coli (40). However, the NtrB-NtrC system is less well characterized in R. rubrum, although an ntrBC mutant has been examined (59). It was expected that some NtrB-NtrCregulated gene expression should be altered in R. rubrum glnD mutants.…”
Section: Vol 187 2005mentioning
confidence: 99%
“…It is possible, therefore, that the PII protein is also involved in the signal pathway leading to the reversible ADP-ribosylation of the iron protein in A. brasilense. ntrBC mutants of A. brasilense (17,24) and R. rubrum (20) failed to inactivate the iron protein by ADP-ribosylation upon addition of NH 4 ϩ but did switch off under anaerobiosis and in darkness, respectively. These results suggested that the ammonium-and energy-triggered pathways for nitrogenase activity control are different.…”
mentioning
confidence: 99%
“…Addition of L-methione-DL-sulfoximine (MSX), a specific glutamine synthetase inhibitor, to derepressed cells prevented nitrogenase switch-off by ammonium, suggesting that glutamine synthetase or glutamine may be part of the signal pathway to DRAT and DRAG (4,10,13,26). Moreover, ntrC mutants of A. brasilense and R. rubrum are incapable of ADPribosylation (17,20,25) (15) at 30°C at 120 rpm. Plasmid pJI1 was constructed by cloning a 0.37-kbp SacI-HindIII DNA fragment containing the A. brasilense glnZ gene into the vector pLAFR3.18.…”
mentioning
confidence: 99%
“…With respect to NSP bacteria, previous studies had indicated that single nucleotide mutations occur at a number of key loci in genes that encode elements of the nitrogen regulatory cascade (Drepper et al, 2003;Hübner et al, 1993;Paschen et al, 2001;Wall & Gest, 1979;Zhang et al, 1995;Zinchenko et al, 1997), as well as at other places on the chromosome (Edgren & Nordlund, 2004;Kern et al, 1998;Masepohl et al, 2002). These changes alter basic control mechanisms resulting in potential derepression of the nitrogenase complex during normal repressive growth conditions.…”
Section: Discussionmentioning
confidence: 99%